2016
DOI: 10.1109/tlt.2015.2444374
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Engagement with In-Video Quiz Questions in a Programming Course

Abstract: In-video quizzes are common in many distance learning platforms, including those from Coursera and EdX. However the effectiveness of in-video quizzes has not previously been assessed. In this paper we describe the construction and instrumentation of an Interactive Video Lecture Platform to measure student engagement with in-video quizzes. We also investigate the use of in-video quizzes as an approach to mitigate the lack of feedback available to students and lecturers in videos and traditional lectures. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…In-video quizzes are even the focus of some recent research (Cummins et al 2015). Quiz question elements can be defined and stored in the database by the educator.…”
Section: Introductionmentioning
confidence: 99%
“…In-video quizzes are even the focus of some recent research (Cummins et al 2015). Quiz question elements can be defined and stored in the database by the educator.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence that the authors provided on the effectiveness of interactive videos when compared to linear non-interactive versions, interactive videos were not really adopted in educational settings or research efforts in the years to follow. It was until recently and most likely due to the technological evolution of web video players that interactive videos enriched with in-video quizzes made their appearance again and have been the focus in a number of research studies (Cummins, et al, 2015;Wachtler et al, 2016;Kohen et al, 2016). Cummins et al research results demonstrated that in-video quizzes were successful in creating an engaging and interactive mode of content delivery.…”
Section: Interactive Videosmentioning
confidence: 99%
“…Researchers have attempted to create videos in programming courses, such as Prolog language, C#, etc. [4], [27]. Students who attended classes found videos equally important to students who do not and seem to prefer videos over a classic textbook [27].…”
Section: Screencasts For Programmingmentioning
confidence: 99%
“…Students who attended classes found videos equally important to students who do not and seem to prefer videos over a classic textbook [27]. In addition, it is demonstrated that student engagement increases, especially when screencasts are associated with in-video quiz questions [4]. The outcome comes into alignment with [24] who showed that interactive dynamic visualisations allow learners to acquire the necessary skills in less time than those who do not interact.…”
Section: Screencasts For Programmingmentioning
confidence: 99%
See 1 more Smart Citation